Keanekaragaman dan Pola Zonasi Ekosistem Mangrove di Desa Otiola Kecamatan Ponelo Kepulauan - Kilinau, Kasim; Sahami, Femy M; Nursinar, Siti (The NIKe Journal, 2023)
This research aims to determine the diversity and zoning patterns of mangroves in Otiola Village, Ponelo Islands District, North Gorontalo Regency. Data collection was carried out from January to February 2021. The sampling method used quadrant line transects and the method for determining mangrove zoning was based on three zoning divisions, namely, proximal, middle and distal. The research location is divided into 4 stations, and each station consists of 5 transect lines. Diversity was calculated using the Simpson Diversity Index formula. The research results show that in Otiola Village there are 20 types of mangroves. The diversity index for the tree category is in the medium to high category (0.632 – 0.873) and for the sapling level it is in the low, medium to high category (0.489 – 0.876), while the seedlings are in the medium to high category (0.674 – 0.831). The mangrove zoning in Otiola Village is classified as impure zoning because there are several species that vary in each zoning (mixed).